The role of the NK-homeobox gene slouch (S59) in somatic muscle patterning - Knirr, Stefan; Azpiazu, Natalia; Frasch, Manfred (Development, 1999)
In the Drosophila embryo, a distinct class of myoblasts, designated as muscle founders, prefigures the mature pattern of somatic body wall muscles. Each founder cell appears to be instrumental in generating a single larval muscle with a defined identity. The NK homeobox gene S59 was the first of a growing number of proposed 'identity genes' that have been found to be expressed in stereotyped patterns in specific subsets of muscle founders and their progenitor cells and are thought to control their developmental fates, In the present study, we describe the effects of gain- and loss-of-function experiments with S59. We find that a null mutation in the gene encoding S59, which we have named slouch (slou), disrupts the development of all muscles that are derived from S59-expressing founder cells. The observed phenotypes upon mutation and ectopic expression of slouch include transformations of founder cell fates, thus confirming that slouch (S59) functions as an identity gene in muscle development. These fate transformations occur between sibling founder cells as well as between neighboring founders that are not lineage-related. In the latter case, we show that slouch (S59) activity is required cell-autonomously to repress the expression of ladybird (lb) homeobox genes, thereby preventing specification along the 2b pathway. Together, these findings provide new insights into the regulatory interactions that establish the somatic muscle pattern.
Keywords: slouch; Drosophila; myoblast; homeobox; ladybird